THE ROLE OF MANAGEMENT INFORMATION SYSTEMS IN SEABANK APPLICATIONS - Faeni, Dewi Puspaningtyas; Sefianggraini , Diah Ayu (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The development of the science and practice of management information systems (MIS) has had a significant impact on management decision-making models, both at the operational and technical implementation levels. In an era of growing global trade, high-quality information and advanced technology are needed to support global enterprises and cooperation. The financial services sector (OJK) is a group of companies and institutions that offer various financial products and services to the public and between institutions. FinTech, which combines the fields of finance and technology, has the aims and benefits of facilitating people's access to financial products, carrying out financial transactions, and increasing financial understanding and literacy.